Juridical Review of Standard Clauses in Goods Expedition Agreements Based on the Consumer Protection Law (Study at the J&T Express Company) - Diana Setiawati; Pradika Dhony Indrawan (Universitas Muhammadiyah Surakarta, 2023)
Goods delivery services are an economic activity that is currently developing very rapidly and always prioritizes aspects of efficiency for its users. Users of goods delivery services are consumers of goods delivery services. The implementation of this efficiency aspect is carried out through the inclusion of standard clauses in goods delivery agreements, this is done to avoid protracted negotiations between business actors and consumers. J&T Express as a goods delivery service business also includes standard clauses. In including standard clauses, J&T Express must pay attention to the provisions in the Consumer Protection Law in the form of a prohibition on the inclusion of certain standard clauses, if the delivery agreement violates the provisions in the Consumer Protection Law it will be declared null and void. This research aims to find out and analyze the standard clauses contained in the J&T Express goods delivery agreement in terms of Law Number 8 of 1999 concerning Consumer Protection (UUPK) and to find out the legal consequences of including these standard clauses. The research method used is a normative juridical approach and descriptive analysis. The research results obtained according to the analysis carried out by the author illustrate that J&T Express, in including standard clauses, transfers responsibility which results in the consumer's rights not being fulfilled, there are several standard clauses which fulfill the elements of Article 18 paragraph (1) UUPK, therefore the legal consequences of the delivery agreement by J&T Express are stated null and void by law, this is in accordance with the provisions of Article 18 paragraph (3) UUPK which states that if there is a standard clause that is not in accordance with the provisions, then it will be declared null and void by law.